Períodos de interferência das plantas daninhas na cultura da soja nos sistemas de semeadura direta e convencional - Nepomuceno, M. [UNESP]; Alves, P.L.C.A. [UNESP]; Dias, T.C.S. [UNESP]; Pavani, M.C.M.D. [UNESP] (Sociedade Brasileira da Ciência das Plantas Daninhas, 2007)
A presente pesquisa objetivou estudar os efeitos dos períodos de controle e de convivência de uma comunidade infestante sobre as características produtivas da soja nos sistemas de semeadura direta (SSD), com o cultivar CD 201, e convencional (SSC), com a MSOY-6101. No SSD, a comunidade infestante foi composta principalmente por Alternanthera tenella, Cenchrus echinatus e Bidens pilosa, com densidade máxima de 377 plantas m-2, acumulando 365,7 g m-2 de matéria seca, e, no SSC, por A. tenella, Senna obtusifolia e Panicum maximum, com densidade máxima de 161 plantas m-2, acumulando 406,7 g m-2. Tolerando cinco por cento de perda na produtividade da cultura, constatou-se que os períodos críticos de prevenção da interferência foram dos 33 aos 66 DAE para o cultivar CD 201 no SSD e dos 34 aos 76 DAE para o cultivar M-SOY-6101 no SSC. A interferência das plantas daninhas durante todo o ciclo da cultura reduziu, em média, 46% (SSD) e 32% (SSC) a produtividade de grãos da soja. Não houve efeito das plantas daninhas na estatura das plantas, na altura de inserção da primeira vagem e no número de vagens por planta.

This work aimed to determine the interference of weed communities in crop yield characteristics, under no-till and conventional till systems. The soybean cultivars used in these experiments were M-SOY - 6101 and CD 201 for conventional and no-till, respectively. The notill system weed community reached its maximum value of 377 plants m-2 28 days after soybean emergence. Maximum dry matter accumulation was 365.7 g m-2, 118 days after emergence, with the main plants being Alternanthera tenella, Cenchrus echinatus and Bidens pilosa. Under the conventional till system, maximum density was 161 plants m-2, 18 DAE and 406.7 g m² of dry matter accumulation at 118 DAE, with the main plants being A. tenella, Senna obtusifolia and Panicum maximum. Accepting losses of 5% in soybean productivity, the CPPI values were estimated to range from 33 to 66 DAE for the no-till system and from 3476 DAE for the conventional till system. Weed interference during the full crop cycle reduced, in average, 46 and 32% of productivity under the no- till and conventional till systems, respectively. No effects were observed on plant height, first pod insertion height, and number of pods per plant due to the presence of weed community.
Periods of weed interference in soybean under tillage and no-tillage systems
Keywords: Competition; Glycine max; control periods; Competição; Glycine max; períodos de controle